Predictive value of plasma human chorionic gonadotropin measured 14 days after Day‐2 single embryo transfer. (19th May 2017) - Løssl, Kristine; Oldenburg, Anna; Toftager, Mette; Bogstad, Jeanette; Prætorius, Lisbeth; Zedeler, Anne; Yding andersen, Claus; Grøndahl, Marie L.; Pinborg, Anja
Abstract: Introduction: Prediction of pregnancy outcome after in vitro fertilization is important for patients and clinicians. Early plasma human chorionic gonadotropin (p‐hCG) levels are the best known predictor of pregnancy outcome, but no studies have been restricted to single embryo transfer (SET) of Day‐2 embryos. The aim of the present study was to investigate the predictive value of p‐hCG measured exactly 14 days after the most commonly used Day‐2 SET on pregnancy, delivery, and perinatal outcome. Material and methods: A retrospective analysis of prospectively collected data on 466 women who had p‐hCG measured exactly 14 days after Day‐2 SET during a randomized trial including 1050 unselected women (aged 18–40 years) undergoing their first in vitro fertilization/ intracytoplasmic sperm injection treatment. Results: The p‐hCG predicted clinical pregnancy [area under the curve (AUC) 0.953; 95% CI 0.915–0.992] significantly better than ongoing pregnancy (AUC 0.803, 95% CI 0.717–0.890) and delivery (AUC 0.772, 95% CI 0.691–0.854). Women with p‐hCG levels in the lowest quartile had significantly lower clinical pregnancy, ongoing pregnancy, and delivery rates ( p < 0.001), whereas the pregnancy outcome and post‐clinical pregnancy loss remained similar throughout the three highest p‐hCG quartiles. The p‐hCG level was related to neither birthweight nor gestational age at delivery. Conclusions: Clinical pregnancy is significantly better predicted by p‐hCG compared with ongoing pregnancy and delivery. Clinical pregnancy rates, ongoing pregnancy rates, and delivery rates remained similar throughout the three highest p‐hCG quartiles with no trend towards "the higher the better".